Preparation and application of metal foam-supported double spinel oxide CuCo2O4-Co3O4 and its derivatives

By preparing and heat-treating it on a foam metal substrate to form a three-dimensional chrysanthemum CuCo2O4-Co3O4 structure, the problems of low efficiency and high cost in existing electrocatalysts in alkaline electrolytes are solved, and efficient, clean and economical hydrogen production is achieved.

CN115505958BActive Publication Date: 2025-04-04WUHAN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211211688.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-30
Publication Date
2025-04-04
Estimated Expiration
2042-09-30

AI Technical Summary

Technical Problem

When existing electrocatalysts are used in alkaline electrolytes to produce hydrogen by electrolyzing water, they are low efficiency and high cost, making it difficult to achieve efficient, clean and economical hydrogen production.

Method used

Using foam metal-loaded double spinel oxide CuCo2O4-Co3O4 and its derivatives, Co(OH)2 nanowires were prepared on a foam metal substrate, CuCo layered double hydroxide was further prepared, and a three-dimensional chrysanthemum CuCo2O4-Co3O4 structure was formed by heat treatment.

Benefits of technology

The high surface area and active sites of the material are achieved, the diffusion of reactants and the generated gas is promoted, the catalytic activity and electrochemical stability of the electrocatalyst are significantly improved, and the excellent overpotential properties and a small Tafel slope are provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003875318340000011
    Figure HDA0003875318340000011
  • Figure HDA0003875318340000012
    Figure HDA0003875318340000012
  • Figure HDA0003875318340000021
    Figure HDA0003875318340000021
Patent Text Reader

Abstract

The present invention provides a preparation and application of a foam metal-supported double spinel oxide CuCo2O4-Co3O4 and its derivatives. First, Co(OH)2 nanowires are prepared on a foam metal substrate by a one-step hydrothermal method to obtain Co(OH)2 / MF; then, CuCo layered double hydroxides are grown on the surface of the Co(OH)2 nanowires by a hydrothermal method to obtain CuCo LDH-Co(OH)2 / MF; then, CuCo LDH-Co(OH)2 / MF is annealed in air by a low-temperature oxidation method to finally obtain a three-dimensional chrysanthemum-shaped CuCo2O4-Co3O4 / MF. The present invention forms a three-dimensional chrysanthemum-shaped structure composed of one-dimensional nanowires through the design and regulation of the carrier-active component. Every few nanowires are interconnected and touch each other. The unique structure provides more active sites, making it easier to discharge oxygen. In addition, the interlacing of the lattice changes the electronic structure inside the material and improves the inherent activity of the electrocatalyst; in Co3O4 with a spinel structure, the Co at the octahedral site III The formed Co‑O serves as the active site for OER, which enhances the electrocatalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano composite materials, and in particular to the preparation and application of a foam metal-loaded double spinel oxide CuCo2O4-Co3O4 and its derivatives. Background Art

[0002] The overuse of fossil energy such as coal, oil and natural gas and their increasing depletion rate have caused global warming and other environmental problems, so it is imperative to develop sustainable and environmentally friendly energy. Hydrogen energy is considered to be the most promising renewable energy source due to its advantages of high efficiency and zero CO2 emissions. However, the low efficiency of hydrogen production by water electrolysis makes efficient and clean hydrogen production technology still a challenge. Generally, the best electrocatalysts for OER reactions in alkaline electrolytes are precious metal-based oxides such as RuO2 and IrO2, but their high cost and low abundance on Earth hinder their application and industrialization. Therefore, it is crucial to develop efficient, cheap and highly stable electrocatalysts.

[0003] Research has found that transition metals and their derivatives are inexpensive and have high catalytic activity, making them very suitable as substitutes for precious metal catalysts. AB2O4 (A, B = transition metal) type spinel oxides composed of 3d transition metals have good electrochemical activity. In the crystal structure of spinel oxides, oxygen is densely packed in a cubic manner, divalent metal cations fill one-eighth of the tetrahedral voids, and trivalent metal cations fill one-half of the octahedral voids. The remaining unoccupied gaps often make the spinel an open structure to accommodate the migration of cations. In addition, the mixed valence of metal cations also helps to provide donor-acceptor sites to adsorb oxygen, thereby promoting the occurrence of water electrolysis reactions. This means that introducing other atoms into the crystal lattice can greatly affect the electronic structure of the original catalyst, thereby enhancing the inherent activity and conductivity of the catalyst.

[0004] In addition, there is another special spinel oxide Co3O4. Due to the large reserves of cobalt, low price and high oxygen evolution efficiency in alkaline solution, Co3O4 spinel oxide is considered to be one of the best OER catalysts. It is generally believed that the 3d empty or half-empty orbital of Co can interact with the π electrons of oxygen and reduce the adsorption energy of O*, HO* and HOO* at the center of the 3d energy band, while the introduction of other atoms can improve the oxygen evolution performance of cobalt-based catalysts, promote the breaking of Co-O bonds and the formation of OO bonds, so as to improve the conductivity of the material and accelerate proton transport. Cu-based electrocatalysts have attracted a lot of attention because Cu-based compounds have similar biomimetic chemical effects to O2. The introduction of Cu into Co-based electrocatalysts can not only change the environment around the 3d orbital and 3d electrons of Co, but also increase the adsorption energy of water and change the Gibbs free energy of adsorbed intermediates, thereby improving the catalytic activity of the catalyst. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a foam metal-supported double spinel oxide CuCo2O4-Co3O4 and its derivatives, the method comprising the following steps: (a) preparing Co(OH)2 nanowires on a foam metal (metal foam, abbreviated as MF) substrate to obtain (Co(OH)2 / MF); (b) using (Co(OH)2 / MF as a raw material to prepare CuCo layered double hydroxide on the Co(OH)2 nanowires to obtain CuCo LDH-Co(OH)2 / MF; (c) placing the CuCo LDH-Co(OH)2 / MF in an oxygen-containing atmosphere for heat treatment to obtain a three-dimensional chrysanthemum-shaped CuCo2O4-Co3O4 / MF.

[0006] Furthermore, step (a) adopts a one-step hydrothermal method to prepare (Co(OH)2 / MF, and the specific process is as follows: dissolve cobalt salt, urea (CH4N2O), NH4F, and polyvinyl pyrrolidone (PVP) in water, then add foam metal, seal and heat to perform hydrothermal reaction, and finally separate the solid and liquid, wash, and dry.

[0007] Furthermore, the cobalt salt in step (a) is specifically one of cobalt sulfate, cobalt chloride, cobalt nitrate, and cobalt acetate, the foam metal is specifically one of foam nickel, foam copper, foam silver, and foam cobalt, the molar ratio of cobalt salt, urea, NH4F and PVP is 1:4-6:1-3:1-3, the hydrothermal reaction temperature is 100-150°C, the hydrothermal reaction time is 4-11h, and after the reaction, the product is repeatedly washed with deionized water for multiple times, and then freeze-dried for 6-8h.

[0008] Furthermore, step (b) adopts a hydrothermal method to prepare CuCo LDH-Co(OH)2 / MF. The specific process is as follows: copper salt, cobalt salt and urea are dissolved in water, and then Co(OH)2 / MF prepared in step (a) is added, and the mixture is sealed and heated for hydrothermal reaction, and finally the solid-liquid separation, washing and drying are performed.

[0009] Furthermore, the copper salt in step (b) is specifically one of copper sulfate, copper acetate, copper chloride, and copper nitrate; the cobalt salt is specifically one of cobalt sulfate, cobalt chloride, cobalt nitrate, and cobalt acetate; the molar ratio of copper salt, cobalt salt, and urea is 1:1-3:9-11; the hydrothermal reaction temperature is 100-150°C; the hydrothermal reaction time is 5-11h; and after the reaction, the product is repeatedly washed with deionized water for multiple times and then fully freeze-dried.

[0010] Furthermore, step (c) adopts a low-temperature oxidation method to prepare a three-dimensional daisy-shaped CuCo2O4-Co3O4 / MF. The specific process is as follows: in an oxygen-containing atmosphere, CuCo LDH-Co(OH)2 / MF is heated for annealing and finally cooled to room temperature.

[0011] Furthermore, the oxygen-containing atmosphere is specifically one of air atmosphere and pure oxygen atmosphere, the heating and cooling rates during the annealing process are both 3-8°C / min, the annealing temperature is 300-800°C, and the holding time is 1-7h.

[0012] The second object of the present invention is to provide a series of foam metal-loaded double spinel oxides and their derivatives, including three types: Co(OH)2 / MF, CuCo LDH-Co(OH)2 / MF, and CuCo2O4-Co3O4 / MF; wherein Co(OH)2 / MF is in the shape of a sea urchin ball, which is surrounded by nanowires, and the endpoints of the nanowires are connected to each other; CuCo LDH-Co(OH)2 / MF presents a chrysanthemum-like structure; CuCo2O4-Co3O4 / MF is a clustered flower ball structure, the petals of which are formed by a plurality of groups of one-dimensional Co(OH)2 nanowires, the bottom ends of the petals are connected to each other, and the outer ends of the petals are connected to the outer ends of the petals of another flower.

[0013] The third object of the present invention is to provide the application of the above-mentioned foam metal-supported double spinel oxide and its derivatives in the electrolysis of water to produce hydrogen.

[0014] Compared with the prior art, the beneficial effects of the present invention are embodied in the following aspects:

[0015] (1) The three prepared metal foams loaded with bi-spinel oxides and their derivatives all have a special three-dimensional (3D) structure, which can increase the surface area and active sites of the materials to a greater extent, and promote the diffusion of reactants and generated gases. The 3D chrysanthemum-like morphology of CuCo2O4-Co3O4 / MF forms outward active sites and a huge specific surface area, which greatly accelerates electron transfer and is more conducive to the rapid desorption of generated oxygen;

[0016] (2) The two spinel oxides (CuCo2O4-Co3O4 / MF) have a more open structure, which is easy for the migration of metal cations. At the same time, the mixed crystal structure improves the mobility of electrons.

[0017] (3) The nanoarrays grown directly on the substrate surface by the self-supporting electrodes give the catalyst a larger surface area and release carriers more quickly, thereby strengthening the interaction and synergistic effect between the species; at the same time, the CuCo2O4 and Co3O4 bimetallic oxides produce a synergistic effect, thereby adjusting the electronic structure and improving the activity of the catalyst;

[0018] (4) The prepared CuCo2O4-Co3O4 / MF does not require a conductive polymer and can be used directly as an electrode;

[0019] (5) The prepared CuCo2O4-Co3O4 / MF has excellent OER catalytic performance. The experimental results show that it has -2 The overpotential under the condition is as low as 267 mV, and the Tafel slope is small (114.59 mV·dec -1 ) and has a high electrochemical surface area (C dl =26.68mF / cm 2 ), has good electrochemical stability in alkaline electrolyte;

[0020] (6) The preparation method provided by the present invention is simple to operate, the raw materials are readily available and inexpensive, and the reaction conditions are easy to achieve, thus having great prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The scanning electron microscope images of Co(OH)2 / NF(a), CuCo LDH-Co(OH)2 / NF(b), and CuCo2O4-Co3O4 / NF(c) prepared in Example 1 are shown respectively;

[0022] Figure 2 They are the full XPS spectrum (a), Cu 2p (b), Co2p (c) and O1s (d) of the CuCo2O4-Co3O4 / NF prepared in Example 2;

[0023] Figure 3 OER polarization curves (a) and corresponding Tafel curves (b) of CuCo2O4-Co3O4 / NF, CuCo LDH-Co(OH)2 / NF, CuCo2O4 / NF, Co3O4 / NF, CuO-Co3O4 / NF, Co3O4-Co3O4 / NF, RuO2 / NF and pure NF prepared in 1M KOH aqueous solution, respectively. DETAILED DESCRIPTION

[0024] In order to enable ordinary technicians in the field to fully understand the technical solutions and beneficial effects of the present invention, further description is given below in conjunction with specific embodiments and drawings.

[0025] Example 1

[0026] a. First, cut nickel foam (NF) into pieces with a geometric area of ​​1×3cm 2 Put the small pieces of nickel foam into a clean beaker, then pour a certain amount of anhydrous ethanol to immerse the nickel foam, and ultrasonically clean it for 20 minutes. After cleaning, use the same method to immerse the nickel foam in 2mol / L hydrochloric acid, ultrasonically clean it for 20 minutes, and finally rinse the nickel foam with deionized water 2-3 times and dry it for later use.

[0027] b. Weigh 2.811g (10mmol) CoSO4·7H2O, 3.003g (50mmol) CH4N2O and 0.7408g (20mmol) NH4F in turn, add them to 50mL deionized water, and dissolve them by ultrasonic to form a transparent and uniform solution. Take 40mL of this solution and add it to a 50mL polytetrafluoroethylene liner, then put the pre-treated nickel foam in, then put the polytetrafluoroethylene liner into the autoclave and transfer it to the muffle furnace as a whole, seal it and keep it at 120℃ for hydrothermal reaction for 5h. After the reaction is completed, take out the nickel foam, rinse it with deionized water for 3-5 times, and then freeze-dry it for 6-8h. The obtained sample is Co(OH)2 / NF.

[0028] The scanning electron microscope image of Co(OH)2 / NF prepared in this step is as follows: Figure 1 As shown in (a), each sea urchin ball is surrounded by nanowires, and the ends of the nanowires are connected to each other, similar to the target sample.

[0029] c. Weigh 149.814 mg (0.6 mmol) CuSO4·9H2O, 337.32 mg (1.2 mmol) CoSO4·7H2O, and 360.36 mg (6 mmol) CH4N2O in turn, add them to 30 mL of deionized water, and dissolve them by ultrasonication to form a transparent and uniform solution. Pour the solution into a 50 mL polytetrafluoroethylene liner, add the dried Co(OH)2 / NF, then put the polytetrafluoroethylene liner into an autoclave and transfer it as a whole to a muffle furnace, seal it, and heat it at 120°C for 6 hours for hydrothermal reaction. After the reaction is completed, take out the solid sample and rinse it with deionized water 3-5 times to remove the unreacted substances on the surface, then freeze-dry it for 6-8 hours. The sample obtained is named CuCo LDH-Co(OH)2 / NF.

[0030] The scanning electron microscope image of CuCo LDH-Co(OH)2 / NF prepared in this step is as follows: Figure 1 As shown in (b), the spherical shape of the sea urchin disappears during the growth of CuCo LDH and evolves into a flower-like structure, which presents a chrysanthemum-like shape as a whole. This is due to the fact that Cu 2+ The addition of caused its structure to rearrange.

[0031] d. Place CuCo LDH-Co(OH)2 / NF in a quartz boat, place the quartz boat in a tube furnace under air atmosphere, heat to 350°C at a heating rate of 5°C / min and keep warm for 2h, and finally cool to room temperature at the same cooling rate to obtain CuCo2O4-Co3O4 / NF.

[0032] The scanning electron microscope image of CuCo2O4-Co3O4 / NF prepared in this step is as follows: Figure 1 (c) As shown in the figure, the product shows a clustered flower ball structure at low magnification. After magnification, it can be seen that it has a distinct chrysanthemum shape, and the bottom ends of the "petals" are connected to each other, and at the outer end of the "petals", each chrysanthemum is connected to another chrysanthemum; the "petals" of the chrysanthemum are actually composed of nanowires, and the surface of the nanowires is not very smooth. The endpoints of every few nanowires are bundled together, and the bundled nanowires are in contact with nanowires of similar structures at the same time, further increasing the mass transfer pathways. The hierarchical structure composed of one-dimensional nanowires and three-dimensional chrysanthemums greatly increases the surface area of ​​the material, which helps to improve the catalytic activity of the material.

[0033] Example 2

[0034] a. First, cut the nickel foam into pieces with a geometric area of ​​1×3cm 2Put the small pieces of nickel foam into a clean beaker, then pour a certain amount of anhydrous ethanol to immerse the nickel foam, and ultrasonically clean it for 20 minutes. After cleaning, use the same method to immerse the nickel foam in 2mol / L hydrochloric acid, ultrasonically clean it for 20 minutes, and finally rinse the nickel foam with deionized water 2-3 times and dry it for later use.

[0035] b. Weigh 2.811g (10mmol) CoSO4·7H2O, 3.003g (50mmol) CH4N2O and 0.7408g (20mmol) NH4F in turn, add the weighed raw materials into 50mL deionized water, and dissolve them by ultrasonication to form a transparent and uniform solution. Take 40mL of the solution and add it into a 50mL clean and dried polytetrafluoroethylene liner, then put in the pre-treated nickel foam, then put the polytetrafluoroethylene liner into the autoclave and transfer it as a whole to the muffle furnace, seal it and keep it at 120℃ for hydrothermal reaction for 5h. After the reaction is completed, take out the nickel foam, rinse it with deionized water for 3-5 times, and then freeze-dry it for 6-8h. The obtained sample is Co(OH)2 / NF.

[0036] c. Weigh 299.628 mg (1.2 mmol) CuSO4·9H2O, 674.64 mg (2.4 mmol) CoSO4·7H2O and 720.72 mg (12 mmol) CH4N2O in turn, add them to 60 mL deionized water, and dissolve them by ultrasonic to form a transparent and uniform solution. Pour the solution into a 50 mL polytetrafluoroethylene liner, and then put the dried Co(OH)2 / NF into it. Then put the polytetrafluoroethylene liner into the autoclave and transfer it to the muffle furnace as a whole. After sealing, keep it at 120°C for hydrothermal reaction for 6 hours. After the reaction is completed, take out the solid sample and rinse it with deionized water for 3-5 times, and then freeze-dry it for 6-8 hours. The sample obtained is named CuCo LDH-Co(OH)2 / NF.

[0037] d. Place CuCo LDH-Co(OH)2 / NF in a quartz boat, place the quartz boat in a tube furnace under air atmosphere, heat to 350°C at a heating rate of 5°C / min and keep warm for 2h, and finally cool to room temperature at the same cooling rate to obtain CuCo2O4-Co3O4 / NF.

[0038] The XPS spectrum of CuCo2O4-Co3O4 / NF prepared in this step is as follows: Figure 2 As shown in (a), the characteristic peaks of C, O, Co and Cu are shown in the figure. Figure 2 (b) shows that the Cu 2p 3 / 2 orbital, the peaks at 931.91 and 934.12 eV are attributed to Cu +and Cu 2+ ; in Cu 2p 1 / 2 The peaks at 951.43 and 953.99 eV are also attributed to Cu + and Cu 2+ In addition, two satellite peaks (marked as sat.) were observed, located at 941.18 and 960.02 eV, which are Cu 2+ The characteristic satellite peaks of CuCo2O4-Co3O4 / NF indicate that Cu + and Cu 2+ .

[0039] like Figure 2 As shown in (c), two types of Co valence states (Co 2+ and Co 3+ ), the fitting peaks at 778.97 and 793.96 eV correspond to Co 3+ The fitting peaks at 780.26 eV and 795.43 eV correspond to Co 2+ .Cu + , Cu 2+ and Co 2+ 、Co 3+ The emergence of multiple valence states indicates that there is a synergistic effect between Cu and Co. Figure 2 In (d), the O1 peak at 533.41 eV is attributed to absorbed water; the O2 peak at 531.97 eV is mainly caused by crystal defects, chemically adsorbed oxygen or coordinated lattice oxygen; the O3 peak is located at 530.28 eV, which has typical metal oxygen bond characteristics, corresponding to Cu-O and Co-O. Therefore, this distribution of electron density is conducive to enhancing the electron transfer between interfaces, thereby improving the catalytic activity of CuCo2O4-Co3O4 / NF.

[0040] Comparative Example 1

[0041] The preparation method of Co3O4 / NF is as follows:

[0042] a. First, cut the nickel foam into pieces with a geometric area of ​​1×3cm 2 Put the small pieces of nickel foam into a clean beaker, then pour a certain amount of anhydrous ethanol to immerse the nickel foam, and ultrasonically clean it for 20 minutes. After cleaning, use the same method to immerse the nickel foam in 2mol / L hydrochloric acid, ultrasonically clean it for 20 minutes, and finally rinse the nickel foam with deionized water 2-3 times and dry it for later use.

[0043] b. Weigh 2.811g (10mmol) CoSO4·7H2O, 3.003g (50mmol) CH4N2O and 0.7408g (20mmol) NH4F in turn, add the weighed raw materials into 50mL deionized water, and dissolve them by ultrasonication to form a transparent and uniform solution. Take 40mL of the solution and add it into a 50mL clean and dried polytetrafluoroethylene liner, then put in the pre-treated nickel foam, then put the polytetrafluoroethylene liner into the autoclave and transfer it as a whole to the muffle furnace, seal it and keep it at 120℃ for hydrothermal reaction for 5h. After the reaction is completed, take out the nickel foam, rinse it with deionized water for 3-5 times, and then freeze-dry it for 6-8h. The obtained sample is Co(OH)2 / NF.

[0044] c. The obtained Co(OH)2 / NF was placed in a tubular furnace under air atmosphere, heated to 350°C at a heating rate of 5°C / min, kept at this temperature for 2h, and finally cooled to room temperature at the same cooling rate to obtain Co3O4 / NF.

[0045] Comparative Example 2

[0046] The preparation method of CuCo2O4 / NF is as follows:

[0047] a. First, cut the nickel foam into pieces with a geometric area of ​​1×3cm 2 Put the small pieces of nickel foam into a clean beaker, then pour a certain amount of anhydrous ethanol to immerse the nickel foam, and ultrasonically clean it for 20 minutes. After cleaning, use the same method to immerse the nickel foam in 2mol / L hydrochloric acid, ultrasonically clean it for 20 minutes, and finally rinse the nickel foam with deionized water 2-3 times and dry it for later use.

[0048] b. Weigh 149.814 mg (0.6 mmol) CuSO4·9H2O, 337.32 mg (1.2 mmol) CoSO4·7H2O, and 360.36 mg (6 mmol) CH4N2O in turn, add them into 30 mL deionized water, and dissolve them by ultrasonication to form a transparent and uniform solution. Pour the solution into a 50 mL polytetrafluoroethylene liner, add the dried nickel foam, then put the polytetrafluoroethylene liner into the autoclave and transfer it to the muffle furnace as a whole, seal it, and heat it at 120°C for 6 hours for hydrothermal reaction. After the reaction is completed, take out the solid sample and rinse it with deionized water for 3-5 times to remove the unreacted substances on the surface, then freeze-dry it for 6-8 hours. The sample obtained is named CuCo LDH / NF.

[0049] c. The obtained CuCo LDH / NF was placed in a tube furnace under air atmosphere, heated to 350°C at a heating rate of 5°C / min, kept at this temperature for 2h, and finally cooled to room temperature at the same cooling rate to obtain CuCo2O4 / NF.

[0050] Comparative Example 3

[0051] The preparation method of CuO-Co3O4 / NF is as follows:

[0052] a. First, cut the nickel foam into pieces with a geometric area of ​​1×3cm 2 Put the small pieces of nickel foam into a clean beaker, then pour a certain amount of anhydrous ethanol to immerse the nickel foam, and ultrasonically clean it for 20 minutes. After cleaning, use the same method to immerse the nickel foam in 2mol / L hydrochloric acid, ultrasonically clean it for 20 minutes, and finally rinse the nickel foam with deionized water 2-3 times and dry it for later use.

[0053] b. Weigh 149.814 mg (0.6 mmol) CuSO4·9H2O, 337.32 mg (1.2 mmol) CoSO4·7H2O, and 360.36 mg (6 mmol) CH4N2O in turn, add them to 30 mL of deionized water, and dissolve them by ultrasonication to form a transparent and uniform solution. Pour the solution into a 50 mL polytetrafluoroethylene liner, add the dried nickel foam, then put the polytetrafluoroethylene liner into an autoclave and transfer it as a whole to a muffle furnace, seal it, and heat it at 120°C for 6 hours for hydrothermal reaction. After the reaction is completed, take out the solid sample and rinse it with deionized water 3-5 times to remove the unreacted substances on the surface, then freeze-dry it for 6-8 hours. The sample obtained is named Cu LDH-Co(OH)2 / NF.

[0054] c. Place Cu LDH-Co(OH)2 / NF in a quartz boat, place the quartz boat in a tube furnace under air atmosphere, heat to 350°C at a heating rate of 5°C / min and keep warm for 2h, and finally cool to room temperature at the same cooling rate to obtain CuO-Co3O4 / NF.

[0055] Comparative Example 4

[0056] The preparation method of Co3O4-Co3O4 / NF is as follows:

[0057] a. First, cut the nickel foam into pieces with a geometric area of ​​1×3cm 2 Put the small pieces of nickel foam into a clean beaker, then pour a certain amount of anhydrous ethanol to immerse the nickel foam, and ultrasonically clean it for 20 minutes. After cleaning, use the same method to immerse the nickel foam in 2mol / L hydrochloric acid, ultrasonically clean it for 20 minutes, and finally rinse the nickel foam with deionized water 2-3 times and dry it for later use.

[0058] b. Weigh 2.811g (10mmol) CoSO4·7H2O, 3.003g (50mmol) CH4N2O and 0.7408g (20mmol) NH4F in turn, add the weighed raw materials into 50mL deionized water, and dissolve them by ultrasonication to form a transparent and uniform solution. Take 40mL of the solution and add it into a 50mL clean and dried polytetrafluoroethylene liner, then put in the pre-treated nickel foam, then put the polytetrafluoroethylene liner into the autoclave and transfer it as a whole to the muffle furnace, seal it and keep it at 120℃ for hydrothermal reaction for 5h. After the reaction is completed, take out the nickel foam, rinse it with deionized water for 3-5 times, and then freeze-dry it for 6-8h. The obtained sample is Co(OH)2 / NF.

[0059] c. Weigh 337.32mg (1.2mmol) CoSO4·7H2O and 360.36mg (6mmol) CH4N2O in turn, add them to 30mL deionized water, and dissolve them by ultrasonic to form a transparent and uniform solution. Pour the solution into a 50mL polytetrafluoroethylene liner, add the dried Co(OH)2 / NF, then put the polytetrafluoroethylene liner into the autoclave and transfer it to the muffle furnace as a whole, seal it, and heat it at 120℃ for 6h for hydrothermal reaction. After the reaction is completed, take out the solid sample and rinse it with deionized water 3-5 times to remove the unreacted substances on the surface, and then freeze-dry it for 6-8h.

[0060] d. Place the sample obtained in step (c) into a quartz boat, place the quartz boat into a tube furnace under air atmosphere, heat to 350°C at a heating rate of 5°C / min and keep warm for 2h, and finally cool to room temperature at the same cooling rate to obtain Co3O4-Co3O4 / NF.

[0061] Comparative Example 5

[0062] The preparation method of RuO2 / NF is as follows:

[0063] a. First, cut the nickel foam into pieces with a geometric area of ​​1×3cm 2 Put the small pieces of nickel foam into a clean beaker, then pour a certain amount of anhydrous ethanol to immerse the nickel foam, and ultrasonically clean it for 20 minutes. After cleaning, use the same method to immerse the nickel foam in 2mol / L hydrochloric acid, ultrasonically clean it for 20 minutes, and finally rinse the nickel foam with deionized water 2-3 times and dry it for later use.

[0064] b. First, use an electronic balance to weigh 4.0 mg of RuO2 powder (99.90%) and 40 μL of Nafion solution (5wt%), and ultrasonically disperse them in 960 μL of ethanol-water solution (ultrapure water: anhydrous ethanol = 3:1). Then, drop the prepared solution evenly on the cleaned and dried nickel foam, and dry it under an infrared lamp.

[0065] For comparison, the products of Example 2 and Comparative Examples 1-5 were subjected to comparative tests. The tested samples were first activated by cyclic voltammetry (CV) and then activated by 2 mV s -1 The scan rate was tested with a scan range of 0 to 0.70 V (vs. SCE), and 85% iR compensation was performed to eliminate the loss caused by the line. The results are as follows Figure 3 In addition to CuCo2O4-Co3O4 / NF and CuCo LDH-Co(OH)2 / NF, Figure 3 (a) also shows the measurement results of CuCo2O4 / NF, Co3O4 / NF, CuO-Co3O4 / NF, Co3O4-Co3O4 / NF, RuO2 / NF and pure NF. Among them, CuCo2O4-Co3O4 / NF showed excellent activity, requiring only 267 mV overpotential to reach 10 mA cm -2 This performance is much better than CuCo2O4 / NF(η 10 =318mV), Co3O4 / NF(η 10 =299mV), CuO-Co3O4 / NF(η 10 =323mV), Co3O4-Co3O4 / CF(η 10 =288mV), CuCo LDH-Co(OH)2 / NF(η 10 =284mV)、RuO2 / NF(η 10 =339mV) and NF(η 10 =345mV). In addition, CuCo2O4-Co3O4 / NF only needs 407mV overpotential to reach 100mA·cm -2 The high current density further illustrates its excellent OER activity.

[0066] The Tafel slope of each electrode was obtained from the LSV curve, which further explained the kinetic characteristics of the material in the OER process. Figure 3 (b) Compared with CuCo2O4 / NF (155.02 mV·dec -1 ), Co3O4 / NF(135.69mV·dec -1), CuO-Co3O4 / NF (132.26 mV·dec -1 ), Co3O4-Co3O4 / CF(142.53mV·dec -1 ), CuCo LDH-Co(OH)2 / NF (140.87mV·dec -1 ), RuO2 / NF(109.7mV·dec -1 ), NF(140.91mV·dec -1 ), the Tafel slope of CuCo2O4-Co3O4 / NF is significantly lower, only 114.59 mV·dec -1 , which shows that the catalytic material has a faster catalytic reaction rate.

Claims

1. A method for preparing a foam metal-supported double spinel oxide CuCo2O4-Co3O4, characterized in that The method comprises the following steps: (a) Co(OH)2 nanowires were prepared on a foam metal substrate by a one-step hydrothermal method to obtain Co(OH)2 / MF. The specific process is as follows: cobalt salt, urea, NH4F, and PVP were dissolved in water, and then the foam metal was added. The mixture was sealed and heated for hydrothermal reaction. After the reaction, the product was repeatedly washed with deionized water for several times, and then freeze-dried. The Co(OH)2 / MF was in the shape of a sea urchin ball, which was surrounded by Co(OH)2 nanowires, and the ends of the nanowires were connected to each other. (b) Using Co(OH)2 / MF as a raw material, a CuCo layered double hydroxide is prepared on Co(OH)2 nanowires by a hydrothermal method to obtain CuCo LDH-Co(OH)2 / MF. The specific process is as follows: copper salt, cobalt salt and urea are dissolved in water, and then the Co(OH)2 / MF prepared in step (a) is added, and the mixture is sealed and heated to perform a hydrothermal reaction. After the reaction, the product is repeatedly washed with deionized water for multiple times, and then fully freeze-dried; the CuCo LDH-Co(OH)2 / MF has a chrysanthemum-shaped structure; (c) The CuCo LDH-Co(OH)2 / MF is placed in an oxygen-containing atmosphere and heated for annealing, and then cooled to room temperature to obtain a three-dimensional chrysanthemum-shaped CuCo2O4-Co3O4 / MF, wherein the oxygen-containing atmosphere is specifically one of an air atmosphere and a pure oxygen atmosphere, and the heating and cooling rates during the annealing process are both 3-8°C / min, the annealing temperature is 300-800°C, and the insulation time is 1-7h; the CuCo2O4-Co3O4 / MF is a clustered flower ball structure, and the petals are formed by a plurality of groups of one-dimensional Co(OH)2 nanowires, the bottom ends of the petals are connected to each other and bundled together, and the outer ends of the petals are connected to the outer ends of the petals of another flower.

2. The method according to claim 1, characterized in that: In step (a), the cobalt salt is selected from one of cobalt sulfate, cobalt chloride, cobalt nitrate and cobalt acetate, the foam metal is selected from one of nickel foam, copper foam, silver foam and cobalt foam, the molar ratio of cobalt salt, urea, NH4F and PVP is 1:4-6:1-3:1-3, the hydrothermal reaction temperature is 100-150°C, and the hydrothermal reaction time is 4-11h.

3. The method according to claim 1, characterized in that: In step (b), the copper salt is selected from one of copper sulfate, copper acetate, copper chloride and copper nitrate, the cobalt salt is selected from one of cobalt sulfate, cobalt chloride, cobalt nitrate and cobalt acetate, the molar ratio of copper salt, cobalt salt and urea is 1:1-3:9-11, the hydrothermal reaction temperature is 100-150° C., and the hydrothermal reaction time is 5-11 hours.

4. A foam metal supported double spinel oxide catalyst, characterized in that: The catalyst is prepared according to any one of the methods of claims 1-3, and the catalyst comprises Co(OH)2 / MF, CuCo LDH-Co(OH)2 / MF, and CuCo2O4-Co3O4 / MF.

5. Use of the foam metal supported bi-spinel oxide catalyst according to claim 4 in hydrogen production by water electrolysis.

Citation Information

Patent Citations

  • Foamy copper loaded nickel-molybdenum-phosphorus-based composite material and preparation method and application thereof

    CN113684497A